BUDAYA POLITIK PEREMPUAN PESISIR: STUDI PERILAKU POLITIK PEREMPUAN DI KABUPATEN INDRAMAYU - Iis Khaerunisah; M. Japar; Suhadi Suhadi (Jurnal Ilmiah Mimbar Demokrasi, 2018)
This study aims to explain the political culture of Indramayu women through political behaviour and political orientation. The method used is descriptive method with qualitative approach. Data collection was carried out through observation, literature studies, and in-depth interviews. The results of the study show that women’s political participation in Indramayu is quite high, especially in the legislatives and excecutive institutions. However, women politicians have not succeeded in fighting for the maximum issue of womens. This happens because of their limited ability and knowledge of the problem that arise. Most female politicians do not have adequate education. They appear as politicians instaneously who rely on the influence of family or relatives who dominate the local bureaucracy.